Exploring relationships between driving events identified by in-vehicle data recorders, infrastructure characteristics and road crashes. (June 2018) - Gitelman, Victoria; Bekhor, Shlomo; Doveh, Etti; Pesahov, Fany; Carmel, Roby; Morik, Smadar
Highlights: We examined relations between IVDR-based driving events, road characteristics and crashes. Different relations were found for various types of events on various road types. More speed events reflect better road conditions and are negatively related to crashes. More braking events indicate road layout constraints and are positively related to crashes. Abstract: There is an increasing interest in technology-based solutions that can assist drivers in reducing their risk of involvement in road crashes. Previous studies showed that driving events produced by in-vehicle data recorders (IVDR) are applicable for identification of unsafe driving patterns, while combined examinations of driving events and road infrastructure characteristics are rare. This study explored the relationship between the IVDR-driving events, road characteristics and crashes, to examine a potential of the events for predicting crashes and identification of high-risk locations on the road network. The study database included 3500 segments of the interurban roads in Israel, for which the automatically produced IVDR events were matched with road infrastructure characteristics and crashes. Negative-binomial regression models were adjusted for the relationships between road characteristics and driving events, and subsequently, between events and crashes, given the exposure. Significant impacts were found, yet various event types showed different relations to the infrastructure characteristics and different effects on crashes, on various road types. Better road conditions were associated with a decrease in "braking" events and an increase in the "speed alert" events, where road layout constraints and junction proximity were associated with an opposite effect on events. "Braking" and total events showed better potential for predicting crashes on single-carriageway roads, with a positive link to crashes, where for other road types the "speed alert" events were stronger related to crashes, but with a negative link. The heterogeneity of findings indicates a need in further research of the above relationship, with a particular focus on definitions of driving events produced by the IVDR or other technologies.